2021
DOI: 10.2147/dmso.s312021
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Peripheral to Central Neuropathy: Examination of Nerve Conduction Combined with Olfactory Tests in Patients with Type 2 Diabetes

Abstract: Few studies have investigated the associations between diabetic peripheral neuropathy (DPN) and cognitive decline. Olfactory impairment is related to neurodegenerative diseases and type 2 diabetes mellitus (T2DM); however, the cognitive alterations of patients with DPN and the role of olfactory function in DPN are not known. We explored alterations in cognition with DPN and the associations of neuropathy parameters with cognition and olfaction. Methods: Healthy controls (HCs) and patients with T2DM underwent n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…It directly leads to changes in sensory function, abnormal feelings, and progressive numbness, and increases the risk of foot ulceration, amputation, cognitive dysfunction, and economic burden. 5,6 Previous studies show that the prevalence of DPN among patients with type 2 diabetes accounts for 2.0-78.8%, depending on the country, duration of diabetes, and examination methods. 1,[7][8][9] Nerve damage not only leads to loss of feeling that allows injuries to go unnoticed and expandable but also causes serious infections and possible amputations.…”
Section: Introductionmentioning
confidence: 99%
“…It directly leads to changes in sensory function, abnormal feelings, and progressive numbness, and increases the risk of foot ulceration, amputation, cognitive dysfunction, and economic burden. 5,6 Previous studies show that the prevalence of DPN among patients with type 2 diabetes accounts for 2.0-78.8%, depending on the country, duration of diabetes, and examination methods. 1,[7][8][9] Nerve damage not only leads to loss of feeling that allows injuries to go unnoticed and expandable but also causes serious infections and possible amputations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in persons with diabetes a lower resting state perfusion [ 43 ], worse vasoreactivity and functional connectivity [ 23 , 34 ] were associated with vascular inflammation and microvascular disease [ 36 ], which correlated with worse cognitive performance [ 2 ] and slower walking [ 26 ]. In addition, diabetic peripheral neuropathy was associated with gray matter and cerebellar atrophy, reduced functional connectivity between frontal lobe and motor areas and worse executive function [ 44 , 45 ]. Possible beneficial effects of INI treatment on vasoreactivity in T2DM need confirmation in larger studies.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Ni et al [ 42 ] included 36 T2DM without DPN, 28 with DPN, and 36 healthy subjects, showing for the first time that T2DM subjects with DPN had worse cognitive function with regard to memory and processing speed as compared with those without DPN. Olfactory identification was a mediating factor between nerve conduction and executive function.…”
Section: Potential Mechanisms Associating Diabetes With Olfactory Dysfunctionmentioning
confidence: 99%
“…Olfactory identification was a mediating factor between nerve conduction and executive function. On the basis of these findings, the authors suggested that olfactory status might be indicative of cognitive impairment among people with DPN [ 42 ].…”
Section: Potential Mechanisms Associating Diabetes With Olfactory Dysfunctionmentioning
confidence: 99%